Multimedia and Interactive Tools Foster Engagement in English as a Foreign Language Critical Reading - Rahman Nur, Dedi; Rohman, Abdul; Geroda, Godefridus Bali; Pane, Widi Syahtia; Rachman, Dzul; Pasaribu, Indah Farma; Auliasari, Yasmin; Hiping, Maria Goretti Adella Kornelia Yulianti; Rohmah, Annisa (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In English as a Foreign Language (EFL) education, critical reading is a core competency for developing higher-order thinking, yet many classrooms, particularly in East Kalimantan, still rely on outdated, passive methods. Specific Background: While multimedia and interactive tools offer potential for enhancing engagement, their integration into EFL critical reading remains inconsistent and often misaligned with learning goals. Knowledge Gap: Limited empirical studies apply the Triple E Framework—Engage, Enhance, Extend—in under-resourced, culturally diverse, and large EFL classrooms to specifically foster critical reading skills. Aims: This study investigates how multimedia and interactive tools, guided by the Triple E Framework, influence engagement, comprehension, and motivation in EFL critical reading. Results: Using a mixed-methods approach with 32 students, findings show that over half of the observed lecturers achieved an “exceptional connection” between learning goals and technology use, leading to improved focus, comprehension, and extended learning beyond class. Novelty: This research offers empirical validation of the Triple E Framework in large, diverse EFL contexts, linking teacher digital literacy to effective critical reading instruction. Implications: Results highlight the need for targeted professional development to equip educators with the skills to integrate technology purposefully, ultimately enhancing students’ readiness for academic and global communication. Highlights: Empirical validation of Triple E Framework in large, diverse EFL classrooms. Teacher digital literacy as a key factor for effective technology integration. Multimedia tools boost engagement, comprehension, and learning extension. Keywords: Triple E Framework, EFL, Critical Reading, Multimedia Tools, Student Engagement